Law, Coercion, and Expression: A Review Essay on Frederick Schauer's The Force of Law and Richard McAdams's The Expressive Powers of Law - Rasmusen, Eric (Journal of Economic Literature, 2017)
What is law and why do people obey it? This question from jurisprudence has recently been tackled using the tools of economics. The field of law and economics has long studied how fines and imprisonment affect behavior. Nobody believes, however, that all compliance is motivated by penalties, and it is questionable whether that is even the typical motivation. Two books published in 2015, Frederick Schauer's The Force of Law and Richard McAdams's The Expressive Powers of Law: Theories and Limits, consider alternative motivations—Schauer skeptically and McAdams more sympathetically. While coercion, either directly or in support of internalized norms, seems to dominate law qua law (and not as a mere expression of morality), a considerable portion of law serves other uses such as coordination, information provision, expression, and reduction of transaction costs. (JEL C72, D23, D83, K00, K40, Z13)